Functional gellan gum hydrogels and cell based therapies – A novel therapeutic approach for spinal cord injury regeneration - Gomes, E. D. (2014)
[Excerpt] Introduction: Spinal Cord Injury (SCI) remains one of the most devastating diseases of the Central Nervous System, for which there is still no effective treatment. Multidisciplinary approaches such those presented by tissue engineering concepts hold great promise for SCI treatment. In this sense we previously functionalized a gellan gum hydrogel (GG) with a fibronectin derived peptide - GRGDS.1 Moreover, it was already demonstrated that Adipose Mesenchymal Stem Cells (ASCs) secrete factors that promote neuronal proliferation; in addition, Olfactory Ensheathing Cells (OECs) are well known for promoting neuronal regeneration and guidance. Furthermore, our group has shown that ASCs and OECs present positive interactions.2 Therefore, we propose to conjugate GG-GRGDS hydrogel with ASCs and OECs in order to promote SCI repair. [...]